2014
DOI: 10.1002/2014jd021734
|View full text |Cite
|
Sign up to set email alerts
|

Climatological characteristics of fronts in the western North Pacific based on surface weather charts

Abstract: Composite front climatology in the western North Pacific is determined using a newly developed 1.0°gridded data set. Here we propose a research strategy for determining the spatiotemporal distribution of fronts using weather chart images published by the Japan Meteorological Agency, one of the major data providers in the region. A preliminarily investigation of the internal data characteristics for the period of 2000-2010 is undertaken, and the final 4 years of data are used for an analysis of front climatolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
(55 reference statements)
1
12
0
Order By: Relevance
“…Utsumi et al. (2014) found that cold fronts around Japan are, on average, longer during winter than during summer. Simmonds et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utsumi et al. (2014) found that cold fronts around Japan are, on average, longer during winter than during summer. Simmonds et al.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of other studies since then investigating fronts from a climatological perspective (e.g., Sinclair 2013; Solman and Orlanski 2014; Rudeva and Simmonds 2015; Utsumi et al. 2014; Schemm et al. 2015; Parfitt et al.…”
Section: Introductionmentioning
confidence: 99%
“…Tuning parameters (thresholds) for the objective detection were determined so that the climatology of objectively detected weather system was consistent with that computed from best track data [ Knapp et al ., ], surface weather charts, and gridded front data set based on surface weather charts [ Utsumi et al ., ], for the TCs, ExC‐centers, and fronts, respectively. Further technical details of the parameter tunings are included in Text S1.…”
Section: Methodsmentioning
confidence: 99%
“…2a) features cyclonic circulations over Mindanao Island and in the broad North Pacific along 20-50°N centered around 45°N, 180°. It is worth mentioning that cold fronts are usually depicted at 925 hPa level (e.g., Utsumi et al 2014) and since the JAN2017 HRF event is associated with a frontal system, we used this pressure level to illustrate the large-scale circulation features throughout the manuscript. Nevertheless, we confirmed that similar circulation features can be depicted at 850 hPa level.…”
Section: Large-scale Circulation Features During the Jan2017 Hrf Eventmentioning
confidence: 99%